Laser tonsillectomy as a treatment on chronic tonsillitis: a case report - Fakhriani, Rizka; Amsriza, Fadli Robby; Widuri, Asti; Daniswara, Deoni (Science Midwifery, 2024)
Tonsillectomy is one of the most often conducted surgical procedures in children. It has several surgical techniques, such as tonsillectomy with thermal welding, guillotine excision, electrocautery, cryosurgery, coblation, ultrasonic removal, laser removal, monopolar and bipolar surgery, and tonsillectomy with ligatures. This case report aims to present a detailed description of a 9-year-old boy who is suffering from tonsillitis. The patient came to the Ear, Nose, and Throat (ENT) clinic with a chronic history of reoccurring throat pain over the past two years, which has lately intensified over the past six months. Complaints are experienced nearly monthly, occasionally accompanied by pain while swallowing, coughing, and a runny nose. The patient experiences a laser-assisted surgical procedure to remove the tonsils. We performed a surgical procedure to excise the tonsil mass using a gallium aluminum arsenide (GaAlAs) diode laser with a wavelength of 980nm/1470nm and a power of 4 watts. This procedure was successfully performed. After laser tonsillectomy treatment on days 1-3, the Visual Analog Scale (VAS) score was 1, indicating no bleeding. On the fourth day, the patient had no pain or bleeding.